2017
DOI: 10.1208/s12248-017-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and Storage Stability of Extracellular Vesicles for Therapeutic Applications

Abstract: Recently, extracellular vesicles (EVs)-including exosomes, microvesicles, and others-have attracted interest as cell-derived biotherapeutics and drug delivery vehicles for a variety of applications. This interest stems from favorable properties of EVs, including their status as mediators of cell-cell communication via transfer of biological cargo and their reported ability to cross biological barriers that impede many delivery systems. However, there are many challenges to translation and widespread applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
239
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(255 citation statements)
references
References 44 publications
3
239
0
Order By: Relevance
“…Indeed, studies have shown that EVs retain function after lyophilization 81,82. Although less clinically feasible, Lipo‐NPs could alternatively be stored at −80 °C (for up to two years), as studies have shown that both EVs and lipoproteins remain stable under such conditions 83,84…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies have shown that EVs retain function after lyophilization 81,82. Although less clinically feasible, Lipo‐NPs could alternatively be stored at −80 °C (for up to two years), as studies have shown that both EVs and lipoproteins remain stable under such conditions 83,84…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, clinical applications of MSC-EVs require their long-term use and considerable thought must be given to the preservation of their immunosuppressive potential [21]. A large number of studies demonstrated that the most convenient mode of storage for MSC-EVs remains −80 • C [109]. Nevertheless, due to the complex cold chain logistics, alternatives such as lyophilization and the incorporation of additives might be necessary to improve MSC-EV storage stability during transportation [21,109].…”
Section: Discussionmentioning
confidence: 99%
“…Freeze/thaw cycles should be minimized, although it has been reported that EVs are relatively stable after several cycles . In this context, cryoprotectants such as trehalose, already used for labile proteins, vaccines, and liposomes, appear to have a positive impact on EVs . Additionally, Frank et al reported that freeze‐drying does not significantly impact the size and particle number of MSC‐derived EVs and that, upon addition of cryoprotecting sugars, the enzymes in the lyophilized EVs have comparable activity to the ones in EVs stored at −80 °C.…”
Section: Storage and Stabilitymentioning
confidence: 99%